2020
DOI: 10.1038/s41401-020-0462-y
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin alleviates sepsis-induced multiple organ dysfunction in mice via inhibiting p38 MAPK/MK2 signaling

Abstract: Sepsis-induced multiple organ dysfunction and inflammatory response are life-threatening symptoms without effective treatment. Fisetin, a dietary flavonoid extracted from berries and family Fabaceae, has displayed neuroprotective and anti-oxidant activities. In this study we investigated whether fisetin exerted a protective effect against sepsis-induced multiple organ dysfunction in mouse cecum ligation and puncture (CLP) model. The mice were injected with fisetin (10 mg/kg, ip) 0.5 h prior to CLP, and sacrifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…To identify small molecules facilitating the induction of NCCs to differentiate into CEC destined cells, we built a chemical library of 30 small molecules that targeted almost all the key pathways of stem cell differentiation and corneal development ( Table 1 ). The final concentration of each compound added to the medium was based on previously reported data and testing for the ED50s in the NCCs via Cell Counting Kit-8 (CCK-8) assay ( Miner et al, 2003 ; Bouzakri et al, 2004 ; Moreno et al, 2008 ; Johnson et al, 2012 ; Yap et al, 2012 ; Cho et al, 2013 ; Han et al, 2014 ; Schelleman et al, 2014 ; Kampa-Schittenhelm et al, 2017 ; Pinkosky et al, 2020 ; Zhang et al, 2020 ; Gampala et al, 2021 ; Ma et al, 2021 ). For initial screening, NCCs derived from dual-SMAD inhibition of hiPSCs for 6 days were cultured in a 24-well plate and treated with small molecules for another 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…To identify small molecules facilitating the induction of NCCs to differentiate into CEC destined cells, we built a chemical library of 30 small molecules that targeted almost all the key pathways of stem cell differentiation and corneal development ( Table 1 ). The final concentration of each compound added to the medium was based on previously reported data and testing for the ED50s in the NCCs via Cell Counting Kit-8 (CCK-8) assay ( Miner et al, 2003 ; Bouzakri et al, 2004 ; Moreno et al, 2008 ; Johnson et al, 2012 ; Yap et al, 2012 ; Cho et al, 2013 ; Han et al, 2014 ; Schelleman et al, 2014 ; Kampa-Schittenhelm et al, 2017 ; Pinkosky et al, 2020 ; Zhang et al, 2020 ; Gampala et al, 2021 ; Ma et al, 2021 ). For initial screening, NCCs derived from dual-SMAD inhibition of hiPSCs for 6 days were cultured in a 24-well plate and treated with small molecules for another 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…By literature reviewing, we found fisetin can activate multiple signaling pathways including JNK, PPAR γ , and p38MAPK [ 40 , 44 , 45 ]. To further elucidate in which pathway fisetin may regulate the expression of PON2, we screened these classic signaling inhibitors and found that GW9662, an inhibitor of PPAR γ signaling pathway, effectively blocked the upregulation effect of fisetin on PON2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the neonatal hypoxic ischemic encephalopathy models established in 10-day-neonatal Sprague Dawley rats, TAK1/NF-κB signaling was significant increased by oxidative stress and inflammatory responses [ 39 ]. TAK1 was found to be critically involved in sepsis-induced multiple organ dysfunction [ 40 ]. DSS-induced colitis was also revealed to be mediated by TAK1 activity in its pathology, containing clinical manifestations, histopathological damage, loss of tight junction function, and imbalanced intestinal microenvironment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%